(untitled) (Global Journal of Science Frontier Research, 2019)
Nutrient mining due to sub optimal fertilizer use in one hand and unbalanced fertilizer (only N and P) uses on other has favored the emergence of multi nutrient deficiency in Ethiopian soils. This problem demands different studies to balance the nutrient combination to improve potato yield and quality. A trial was conduct to evaluate different fertilizer types for potato production and to enrich its quality in Southern Ethiopia during the main cropping season of 2016 and 2017. Fertilizer treatments were based on limiting nutrients of the area including N, P, K, S, B and at different rate and cobination. The trial consists of ten treatments (1) no fertilizer (control) (2) NPSB: 69 kg N + 23.5 kg P + 10 kg S + 1.07 kg B/ha (3) NPSB: 92 kg N + 31 kg P + 13 kg S + 1.4 kg B/ha (4) NPSB: 115 kg N + 39 kg P + 17 kg S + 1.7 kg B/ha (5) NPSB: 138 kg N + 47 kg P + 20 kg S + 2.0 kg B/ha (6) NPSBCu: 69 kg N + 31 kg P + 17 kg S + 1.4 kg B + 0.625 kg Cu/ha (7) NPSBCu: 92 kg N + 39 kg P + 10 kg S + 1.7 kg B + 0.625 kg Cu/ha (8) NPSBCu: 115 kg N + 39 kg P + 10 kg S + 1.7 kg B + 0.625 kg Cu/ha (9) NPSBCu: 138 kg N + 39 kg P + 10 kg S + 1.7 kg B + 0.625 kg Cu/ha and (10) NPS: 112 kg N + 40 kg P + 17 kg S/ha was used as positive control.